PERANCANGAN APLIKASI QR CODE SEBAGAI MEDIA INFORMASI PENGENALAN SATWA KEBUN BINATANG BERBASIS WEBSITE - Dimas_20 Setiadi; Neny Rosmawarni (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2020)
With the development of technological advances, the internet is a means of infrastructure not only for communicating or interacting, in Indonesia alone there are 78 million people who use the internet. QR code or Quick Respone is a matrix code that was first discovered by denso wave in 1994, this QR code has become the world's trending in this modern and digital era. One of the advantages of QR code is that QR code is universal and has little risk of error, zoo is a means for just either recreation or picnic. The zoo itself usually consists of various kinds of animals and primates, the purpose of this research is to make it easier for zoos to introduce their animals by utilizing this QR code technology so that it can simplify and streamline the work of zoo staff and make it easier for visitors to recognize animal species so that development technology can be utilized properly. Keywords : Internet, QR code, Zoo